Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To identify which equation correctly represents the given equation [tex]\( y - 6x - 9 = 0 \)[/tex] in function notation with [tex]\( x \)[/tex] as the independent variable, let's go through the steps to rewrite the equation.
1. Start with the original equation:
[tex]\[ y - 6x - 9 = 0 \][/tex]
2. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = 6x + 9 \][/tex]
3. In function notation, we express [tex]\( y \)[/tex] as [tex]\( f(x) \)[/tex] because [tex]\( y \)[/tex] is dependent on the independent variable [tex]\( x \)[/tex]:
[tex]\[ f(x) = 6x + 9 \][/tex]
Given the options:
- [tex]\( f(x) = 6x + 9 \)[/tex]
- [tex]\( f(x) = \frac{1}{6}x + \frac{3}{2} \)[/tex]
- [tex]\( f(y) = 6y + 9 \)[/tex]
- [tex]\( f(y) = \frac{1}{6}y + \frac{3}{2} \)[/tex]
The correct equation written in function notation with [tex]\( x \)[/tex] as the independent variable is:
[tex]\[ f(x) = 6x + 9 \][/tex]
So, the first option [tex]\( f(x) = 6x + 9 \)[/tex] is correct. Therefore, the answer to the question is:
[tex]\[ 1 \][/tex]
1. Start with the original equation:
[tex]\[ y - 6x - 9 = 0 \][/tex]
2. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = 6x + 9 \][/tex]
3. In function notation, we express [tex]\( y \)[/tex] as [tex]\( f(x) \)[/tex] because [tex]\( y \)[/tex] is dependent on the independent variable [tex]\( x \)[/tex]:
[tex]\[ f(x) = 6x + 9 \][/tex]
Given the options:
- [tex]\( f(x) = 6x + 9 \)[/tex]
- [tex]\( f(x) = \frac{1}{6}x + \frac{3}{2} \)[/tex]
- [tex]\( f(y) = 6y + 9 \)[/tex]
- [tex]\( f(y) = \frac{1}{6}y + \frac{3}{2} \)[/tex]
The correct equation written in function notation with [tex]\( x \)[/tex] as the independent variable is:
[tex]\[ f(x) = 6x + 9 \][/tex]
So, the first option [tex]\( f(x) = 6x + 9 \)[/tex] is correct. Therefore, the answer to the question is:
[tex]\[ 1 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.